Small-Molecule Inhibitors of the SOX18 Transcription Factor. Issue 3 (16th March 2017) - Fontaine, Frank; Overman, Jeroen; Moustaqil, Mehdi; Mamidyala, Sreeman; Salim, Angela; Narasimhan, Kamesh; Prokoph, Nina; Robertson, Avril A.B.; Lua, Linda; Alexandrov, Kirill; Koopman, Peter; Capon, Robert J.; et al.
Summary: Pharmacological modulation of transcription factors (TFs) has only met little success over the past four decades. This is mostly due to standard drug discovery approaches centered on blocking protein/DNA binding or interfering with post-translational modifications. Recent advances in the field of TF biology have revealed a central role of protein-protein interaction in their mode of action. In an attempt to modulate the activity of SOX18 TF, a known regulator of vascular growth in development and disease, we screened a marine extract library for potential small-molecule inhibitors. We identified two compounds, which inspired a series of synthetic SOX18 inhibitors, able to interfere with the SOX18 HMG DNA-binding domain, and to disrupt HMG-dependent protein-protein interaction with RBPJ. These compounds also perturbed SOX18 transcriptional activity in a cell-based reporter gene system. This approach may prove useful in developing a new class of anti-angiogenic compounds based on the inhibition of TF activity. Highlights: Novel small-moleculeSm4 inhibits SOX18 protein-protein interaction Transcription factor SOX18 interacts with Notch effector RBPJ Different small molecules inhibit distinct SOX18 protein-protein interactions SOX18-RBPJ interaction, mediated by HMG domain, is modulated by small-moleculeSm4 Abstract : Fontaine et al. describe a novel avenue for manipulating SOX18 transcription factor activity using small-molecule inhibitors. This approach shows that the inhibitors block transcriptional activation by disrupting protein-protein interaction.